Strategies, beliefs, and challenges: A thematic exploration of self-regulated learning - Baissane, Omar; Baissane, Omar (Journal of Interdisciplinary Studies in Education, 2026)
This qualitative study examines English as a foreign language (EFL) students’ perception of self-regulated learning (SRL) strategies and motivational beliefs. Semistructured interviews were conducted with 25 students. Data were analyzed using reflexive thematic analysis. Four key themes emerged from the analysis. These are approaches to goal orientations, perceptions of task value and self-efficacy, cognitive and metacognitive learning strategies, and management of study time and environment. The findings revealed that students combine intrinsic and extrinsic goals, value tasks selectively, and employ varied cognitive, metacognitive, and time-management strategies. In general, Moroccan EFL learners demonstrate notable strengths in self-regulation and motivation.